2015
DOI: 10.1002/2014tc003738
|View full text |Cite
|
Sign up to set email alerts
|

The fracture network, a proxy for mesoscale deformation: Constraints on layer parallel shortening history from the Malargüe fold and thrust belt, Argentina

Abstract: An analysis was performed of the fracture networks in the N-S trending thick-skinned Malargüe fold and thrust belt (MFTB). A total of 2000 planar structures including joints and veins were measured in different structural domains ranging from surficial thin-skinned systems detached in the cover to large-scale structures such as basement-cored folds. The investigated stratigraphic section ranges from the Middle Jurassic (Cuyo Group) to the Paleocene (Malargüe Group), including sandstones, siltstones, shales, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 64 publications
(116 reference statements)
1
22
0
Order By: Relevance
“…Considering the Southern Andes and the particular case of the Malargue Fold–Thrust Belt, a systematically compressive regime recorded in the development of inverted basement structures in the foreland basin (Strecker et al 2011; this study), in the transmission of the crustal shortening in the intrabelt sedimentary cover (Branellec et al 2015 a , Branellec et al this issue) and in the record by meso- and microscale strain indicators such as fracture sets and matrix-scale strain (Branellec et al 2015b) is suggested. This pattern of deformation is also clearly evidenced further north in the Sierra Pampeanas (e.g.…”
Section: Discussionmentioning
confidence: 76%
“…Considering the Southern Andes and the particular case of the Malargue Fold–Thrust Belt, a systematically compressive regime recorded in the development of inverted basement structures in the foreland basin (Strecker et al 2011; this study), in the transmission of the crustal shortening in the intrabelt sedimentary cover (Branellec et al 2015 a , Branellec et al this issue) and in the record by meso- and microscale strain indicators such as fracture sets and matrix-scale strain (Branellec et al 2015b) is suggested. This pattern of deformation is also clearly evidenced further north in the Sierra Pampeanas (e.g.…”
Section: Discussionmentioning
confidence: 76%
“…Fractures networks of foreland settings can either be inherited from former orogenic episodes of deformations, developed during early compression by layer parallel shortening (LPS), or during further sediment burial stages (Engelder & Peacock, ; Bergbauer & Pollard, ; Bellahsen et al ., ; Tavani et al ., ; Branellec et al ., ). In our study, fractures originated from Pyrenean orogeny because studied rocks are syn‐orogenic (upper Cretaceous to upper Eocene).…”
Section: Discussionmentioning
confidence: 97%
“…LPS is widely recognized in foreland basin and fold‐and‐thrust belts (e.g. Bellahsen et al ., ; Beaudoin et al ., ; Branellec et al ., ). In response to LPS, transverse fractures develop before and during early folding.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The K parameter was used to evaluate the degree of clustering during each step of rotation (cf. Branellec et al, 2015) for each vein set using Fisher statistics (Fisher et al, 1987b). K is a dispersion or concentration factor defined by:…”
Section: Fold Tests Structural Trend and Statistical Determination mentioning
confidence: 99%